Features and Colonization Strategies of Enterococcus faecalis in the Gut of Bombyx mori - Zhang, Xiancui; Feng, Huihui; He, Jintao; Muhammad, Abrar; Zhang, Fan; Lu, Xingmeng (Frontiers in Microbiology, 2022)
The complex gut microbiome is a malleable microbial community that can undergo remodeling in response to many factors, including the gut environment and microbial properties. Enterococcus has emerged as one of the predominant gut commensal bacterial genera and plays a fundamental role in the host physiology and health of the major economic agricultural insect, Bombyx mori. Although extensive research on gut structure and microbiome diversity has been carried out, how these microbial consortia are established in multifarious niches within the gut has not been well characterized to date. Here, an Enterococcus species that was stably associated with its host, the model organism B. mori, was identified¬ in the larval gut. GFP–tagged E. faecalis LX10 was constructed as a model bacterium to track the colonization mechanism in the intestine of B. mori. The results revealed that the minimum and optimum colonization results were obtained by feeding at doses of 105 CFU/silkworm and 107 CFU/silkworm, respectively, as confirmed by bioassays and fluorescence-activated cell sorting analyses (FACS). Furthermore, a comprehensive genome-wide exploration of signal sequences provided insight into the relevant colonization properties of E. faecalis LX10. E. faecalis LX10 grew well under alkaline conditions and stably reduced the intestinal pH through lactic acid production. Additionally, the genomic features responsible for lactic acid fermentation were characterized. We further expressed and purified E. faecalis bacteriocin and found that it was particularly effective against other gut bacteria, including Enterococcus casselifavus, Enterococcus mundtii, Serratia marcescens, Bacillus amyloliquefaciens, and Escherichia coli. In addition, the successful colonization of E. faecalis LX10 led to drastically increased expression of all adhesin genes (znuA, lepB, hssA, adhE, EbpA and Lap), defense genes (cspp and esp), and immune evasion genes (patA and patB), while the expression of iron acquisition genes (ddpD and metN) was largely unchanged or decreased. This work establishes an unprecedented conceptual model for understanding B. mori–gut microbiota interactions in an ecological context. Moreover, these results shed light on the molecular mechanisms of gut microbiota proliferation and colonization in the intestinal tract of this insect.